(untitled) (REMUNOM, 2025)
This study reviewed the state of the art of research on betting houses in Brazil, with the aim of identifying contributions and gaps, and proposing a research agenda relevant to the national context. Through an integrative review of 22 studies published between 2020 and 2024, it was possible to map the main themes investigated, including the regulation of the sector, the economic, social, and psychological impacts of betting, as well as issues related to civil liability and bettor behavior. The results show significant advances in understanding the challenges and opportunities associated with the betting market, especially after the implementation of Laws No. 13,756/2018 and No. 14,790/2023. However, there is still a gap between the development of regulatory policies and the mitigation of negative impacts, such as player indebtedness and increased social vulnerability. In addition, the need for studies that explore the interaction between regulation, financial education, and consumer protection was identified. This work highlights the relevance of a research agenda that broadens understanding of the regional and cultural specificities of the Brazilian market, contributing to the formulation of more inclusive and effective public policies.